1983
DOI: 10.1111/j.1151-2916.1983.tb09958.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ultrafine Tetragonal ZrO2 Powder Under Hydrothermal Conditions

Abstract: Ultrafine tetragonal ZrOz powder was prepared by hydrothermal treatment at 100 MPa of amorphous hydrous zirconia with distilled water and LiCl and KBr solutions. The resulting powder consisted of well-crystallized particles; at 2OO0C, the particle size was 16 nm and at 500°C, 30 nm. Under hydrothermal conditions tetragonal ZrOt appears to crystallize topotactically on nuclei in the amorphous hydrous zirconia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(81 citation statements)
references
References 13 publications
7
72
2
Order By: Relevance
“…For example, Uvage at al. 53 attributed the t-Zr0 2 metastability to these structural similarities, while Tani et al 54 proposed a mechanism of "topotactic" crystallization of t-Zr0 2 on nuclei in the amorphous zirconia.…”
Section: °Cmentioning
confidence: 97%
“…For example, Uvage at al. 53 attributed the t-Zr0 2 metastability to these structural similarities, while Tani et al 54 proposed a mechanism of "topotactic" crystallization of t-Zr0 2 on nuclei in the amorphous zirconia.…”
Section: °Cmentioning
confidence: 97%
“…Livage et al [12] ascribe initial formation of the tetragonal phase to the structural similarity between the amorphous and tetragonal form of Zr02. Similarly, Tani et al [13] proposed a mechanism of topotactic crystallization of tetragonal zirconia on nuclei in the amorphous Zr02. Whether the palladium phases influence the stability of the tetragonal zirconia can not be answered from the present study and needs further investigation.…”
Section: Deposition and Incorporation Of Carbonmentioning
confidence: 98%
“…If the crystallite size attains a critical value of 30 nm or above, the tetragonal--, monoclinic transformation is favoured. This theory was questioned by the data of Morgan [21] among others [22][23][24][25][26] who was able to produce 6 nm monoclinic zirconia particles by extensive refluxing of zirconyl chloride solution at pH 1-2. We reported earlier that the precipitation of zirconia at pH 2-4 from zirconyl chloride solution produced ultrafine tetragonal zirconia particles with X-ray crystallite size of about 15-16 nm in size after calcination at 500 ~ for 5 h. It was also reported that this tetragonal phase is transformed to monoclinic phase with increasing calcination time at 500 ~ [12].…”
Section: Crystallite Size Effectmentioning
confidence: 96%